2018
DOI: 10.1186/s12906-018-2382-7
|View full text |Cite
|
Sign up to set email alerts
|

Terminalia bellirica fruit extracts: in-vitro antibacterial activity against selected multidrug-resistant bacteria, radical scavenging activity and cytotoxicity study on BHK-21 cells

Abstract: BackgroundIdentification of novel sources for developing new antibiotics is imperative with the emergence of antibiotic resistant bacteria. The fruits of Terminalia bellirica (Gaertn) Roxb., widely used in traditional medicine, were evaluated for antibacterial activity against multidrug-resistant (MDR) bacteria, antioxidant activity and cytotoxicity.MethodsTwelve solvent extracts of T. bellirica fruits were prepared by direct aqueous extraction and sequential extraction with dichloromethane, methanol and water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 24 publications
2
36
0
Order By: Relevance
“…In contrast, in spontaneously hypertensive rats, the H 2 S-induced actions scarcely depend on nitric oxide release; also, the nitric oxide effects are largely H 2 S-independent and represent the first step for understanding pathophysiological mechanisms of nitric oxide/H 2 S interplays under both normotensive and hypertensive conditions [31]. Terminalia bellirica is also shown to have antihypertensive [17] and antioxidant [32] activity. Curcumae aeruginosae known by the local name of black temu and Amomi fructus (cardamom) have been proven to have antioxidant activity [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in spontaneously hypertensive rats, the H 2 S-induced actions scarcely depend on nitric oxide release; also, the nitric oxide effects are largely H 2 S-independent and represent the first step for understanding pathophysiological mechanisms of nitric oxide/H 2 S interplays under both normotensive and hypertensive conditions [31]. Terminalia bellirica is also shown to have antihypertensive [17] and antioxidant [32] activity. Curcumae aeruginosae known by the local name of black temu and Amomi fructus (cardamom) have been proven to have antioxidant activity [18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…Roxb. ( Dharmaratne et al., 2018 ) and Terminalia chebula Retz. ( Sharma et al., 2012 ) fruit extracts.…”
Section: Updates On the Research On Terminalia Spmentioning
confidence: 99%
“…Roxb. fruits possess antibacterial activity without having cytotoxicity ( Dharmaratne et al., 2018 ). A recent study showed that the aqueous acetone extract of T. bellirica (Gaertn.)…”
Section: Terminalia Sp Medicinal Potential (Folk Medicinal mentioning
confidence: 99%
See 1 more Smart Citation
“…Wight & Arn. have been particularly well studied [21]. In contrast, the Australian Terminalia species remain relatively poorly examined.…”
Section: Terminalia Ferdinandiana Fruit and Leaf Extracts Inhibit Metmentioning
confidence: 99%